Movie recommendation using link prediction - Dhrubo, Md Alif-uz-zaman; Supty, Tasfia Chowdhury; Hossin, Md Rakib; Rahman, SM Ashfaqur; Das, Ananya (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2021.